Bringing climate health conversations to frontline clinics: A qualitative post-intervention assessment of utilization of the Climate Resilience for Frontline Clinics Toolkit - Yi-Ting Hana Lee; Mingyue Ma; Caroline Sarpy; Casey Dai; Jinia Sarkar; Chelsea Heberlein; Theodore Miles; Caleb J. Dresser (The Journal of Climate Change and Health, 2025)
Introduction: Community health centers and clinics are on the frontlines of climate change and adverse health effects, providing essential care to millions of low-income, uninsured, and underinsured populations across the country. The Climate Resilience for Frontline Clinics Toolkit (“the toolkit”) was developed to support frontline clinicians in preparing for climate-related health risks. The objectives of this study were to assess the utilization and challenges in the implementation of the toolkit in real-world clinic settings and to guide further development of clinic-based risk reduction resources. Methods: A qualitative, semi-structured interview and post-intervention assessment approach was used to interview 28 clinicians and staff from 15 clinics across six states. Results: Participants generally found the toolkit valuable, noting that it addressed an unmet need by providing actionable information on climate health risks in resource-constrained settings. However, challenges included information overload, the complexity of patient-facing materials, and concerns about literacy barriers. Many participants felt that the toolkit could benefit from more concise and visually supported materials, as well as adjustments to better align with patient literacy levels. Discussion: These findings highlight the importance of tailoring resources to the specific needs of frontline clinics and their patient populations. Future research should examine the long-term impacts of integrating such resources on patient behaviors and health outcomes and explore strategies for integrating climate resilience into routine clinical care.